Kepemilikan Saham Sebagai Salah Satu Bentuk Ganti Kerugian dalam Pengadaan Tanah Untuk Pembangunan Jalan - Sukma, Andrio Firstiana (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2014)
Land procurement for public purposes which regulated in Law No. 2/2012 aims to provide land for the implementation of development in order to improve the welfare and prosperity of the nation, state, and people with ensuring legal certainty of the rightful owner. A decent and fair compensation should be given in the land procurement. Compensation can be given in cash, land replacement, resettlement, stock or combination of 2 or more compensation forms. Nowadays, usually compensation is given by cash because of it is easy, fast, practical and cheap. However, compensation in stock considered as a promising one because it ensures income for rightful owners. Unfortunately regulation about it is not comprehensive and needs to be completed so it won’t cause a problem in the future. Through qualitative and content analysis there are some things to be clarified, namely state-owned enterprises function in land procurement, minimaum compensation for buying 1 lot of state-owned enterprises stock and the importance of involving fund manager since the beginning.